Aberration retrieval for laser scanning microscopy - Smid, Pieter Henry (2019)
This thesis explores different indirect wavefront sensing methods for detection of primary Zernike aberrations in laser scanning microscopes. All the presented aberration retrieval methods rely on analysing intensity distributions in the focal region and within the first dark ring of the Airy spot.